Gender, Maternity and Deficiency: Representation of Diversity - Welter, Ivânia; Cetolin, Sirlei Fávero; Trzcinski, Clarete; Cetolin, Simone Kelli (Textos & Contextos (Porto Alegre), 2008)
This article is part of a research held in the Social Course of the University of the West of Santa Catarina – UNOESC, Campus of São Miguel do Oeste and had as general objective, identify the principal social representations of mothers with Down Syndrome children. The interest for the presented thematic came from real-life experiences during the Curricular Trainee period, at the Special School “Viviane” – APAE of São José do Cedro-SC. And, also, by the fact of the Social Service to contribute to the professional acting at the problematic situations caused by the mental deficiency. The result of this work was gotten through a field research with 06 mothers with Down Syndrome and, in theoretical referential, in which, were observed the principal social representations that are reflected since the first contact with the deficiency, identified through: the fault, negation/acceptance, in the familiar relationship and, principally, reassured the historic and social condition of the woman/mother as the main tutor of the child with deficiency. Among the strategies for facing the reality that the woman/mother passes by we pointed the contribution of professionals with technical prepare, for example the social assistant who will be able to act in the implantation and implementation of politics in the social inclusion of the person with deficiency and his family. Key words – Family. Woman. Mother. Deficiency. Social representation.